PROYECTO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA EMPRESA PRODUCTORA Y COMERCIALIZADORA DE HELADOS DE CREMA EN LA CIUDAD DE CATACOCHA – CANTÓN PALTAS – PROVINCIA DE LOJA - Eras Yaguana, Albania Marisol (2019)
The main objective of this research work is to determine the feasibility of creating a company that produces and commercializes ice cream in the city of Catacocha - Cantón Paltas - Provincia de Loja, which will serve as a guide to generate a new business project that provide society with a new and innovative product that leads to improve the food habits of the population. In such a way that the specific objectives to be carried out were raised: the market study, technical study, legal administrative study, financial study and finally the evaluation of the project. The methodology used was descriptive where a sample of 373 surveys was determined, the same ones that were applied to the inhabitants of the city of Catacocha. It begins with the market study where the required demands of the project were determined, while for the first year the potential demand represents 67% that if they consume ice cream is 8,662 inhabitants, the actual demand is made up of 96% equivalent to 8,316 respondents who buy cream ice cream, while for effective demand corresponds 100% which is equivalent to 8,316 inhabitants who would be willing to purchase our product; the offer for the first year is zero and the unsatisfied demand is 399,151, with these results marketing strategies focused on the marketing mix (product, price, place and promotion) were proposed. The technical study was drawn up to establish the necessary processes, such as product engineering, plant size, in which the installed capacity that is 100% was determined, allows a production of 525,600 ice creams and the one used is 24% which allows a production of 124,800 units for the first year. The company will be located in the center of the city of Catacocha, in the streets: Alonso de Mercadillo between Lauro Guerrero and Domingo Celi, a place that has access roads and essential basic services. 5 In addition, the legal administrative study was carried out where the organizational structure was defined, with its respective organizational chart, thus determining the manual of functions indicating the tasks for each position, the nature of the work and the requirements that employees must meet to occupy those positions. The financial study described fixed and deferred assets and working capital giving a total investment of $ 15,139.82, which will be financed by the shareholders' capital by 67% and by BanEcuador by 33%. On the other hand, the results obtained determined the feasibility of the project with a NPV of $ 25.636,86; the IRR (Internal Rate of Return) corresponds to $ 50.99%; Rb / c. (Profit Cost Ratio) of $ 1.21 for each dollar invested the company earns 21; the PRC. (Capital Recovery Period) It is 2 years, 8 months and 19 days; A.S (Sensitivity Analysis) indicates that the project supports an increase in costs of 8,70% and a decrease in revenues of 7,22%, therefore the project is feasible, whose conclusions and recommendations thus determine it.